2016
DOI: 10.1179/2046023615y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunohistochemical staining for glucagon in human pancreatic tissue

Abstract: Immunohistochemistry (IHC) and immunofluorescence (IF) staining techniques are important diagnostic tools of anatomic pathology in the clinical setting and widely used analytical tools in research laboratories. In diabetes research, they are routinely used for the assessment of beta- and alpha-cell mass, for assessment of endocrine cell distribution within the pancreas, for evaluation of islet composition and islet morphology. Here, we present the evaluation of IHC techniques for the detection of alpha-cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Immunohistochemical evaluations are therefore indispensable diagnostic tools of anatomical histopathology that gives information on β‐ and α‐cell mass, endocrine cell distribution within the pancreas, islet β‐cell composition and islet morphology in diabetic rats. [ 48 ] In this study, we observed immunohistochemically that streptozotocin significantly reduced endocrine cell distribution and islet β‐cell composition in negative control rats evident by low insulin immunoreactivity in this group. This is in consonance with several reports where STZ was implicated in the induction of these deranged features.…”
Section: Discussionmentioning
confidence: 61%
“…Immunohistochemical evaluations are therefore indispensable diagnostic tools of anatomical histopathology that gives information on β‐ and α‐cell mass, endocrine cell distribution within the pancreas, islet β‐cell composition and islet morphology in diabetic rats. [ 48 ] In this study, we observed immunohistochemically that streptozotocin significantly reduced endocrine cell distribution and islet β‐cell composition in negative control rats evident by low insulin immunoreactivity in this group. This is in consonance with several reports where STZ was implicated in the induction of these deranged features.…”
Section: Discussionmentioning
confidence: 61%